The Management of Economic Decline and the Dimension of Organizational Change - Mihaela Onofrei; Dan Lupu (Amfiteatru Economic)
In the current climate, more and more companies are faced with multiple failures, which are the basic problem that crisis management must resolve. In situations of economic decline, the need for change at the organizational level is imperative to facilitate the recovery of a company. This study aims to identify methods of corporate restructuring, which would be to adopt could be adopted by Romanian companies in a time of crisis, to ensure business sustainability. The research methodology has a theoretical and an empirical component and it is based on statistical methods that facilitated a quantitative approach, using a sample of 82 companies listed on Bucharest Stock Exchange, all of them being declared insolvent between 2000 and 2010. The research results have contributed to the classification of companies, both by generating causes of insolvency and by restructuring methods